Upaya Meningkatkan Ketrampilan Motorik Halus Anak Melalui Kegiatan Kolase Pada Kelompok B TK Salafiyah Moga I Kecamatan Moga Kabupaten Pemalang Semester I Tahun 2021/2022 - Andarini, Diyah (Program Studi S1 PG-PAUD, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Satya Wacana, 2024)
This study aims to improve the fine motor skills of Group B Children of Tk Salafiyah Moga I, Moga District, Pemalang Regency. Because of the problems that show that the fine motor skills of group B children at Salafiyah Moga I Kindergarten are still low. Learning strategies are less varied and learning to stimulate fine motor skills is less than perfect. This is because learning does not provide opportunities for children to express only follow the learning delivered by the teacher. This research uses Classroom Action Research (PTK). The subjects of this study were Group B students of Tk Salafiyah Moga I, Moga District, Pemalang Regency. The results of this study after taking action there is a change towards the better. Seen in each cycle in the learning stages of applying collage techniques from natural materials. The results of observations from the average assessment of fine motor skills tests as a whole class of children in the observation of the new pre-cycle of about 20% in class action research began to increase from cycle I to 40% and increased in cycle II to 80%. Based on the results of the study it can be concluded that through collage techniques can improve fine motor skills in early childhood in Group B Tk Salafiyah Moga I, Moga District, Pemalang Regency.